THE USE OF ANAGRAM TECHNIQUE IN TEACHING VOCABULARY AT SENIOR HIGH SCHOOL IN CIMAHI - Elin Erma Susanti; Ningtyas Orilina Argawati (IKIP Siliwangi, 2022)
Vocabulary is one of the essentials needs for language learning. Likewise, in learning English lack of vocabulary is a problem still faced in learning the English language. The purpose of this research is to describe the use of anagram technique in learning vocabulary. This research was conducted by using descriptive qualitative research methods. The subject of this research consisting of first grade students of Vocational High School at SMK Pusdikhub, consisted of thirty-one male students and two female students during the second semester of the academic year 2019/2020. The researcher collected the data from observation and questionnaire. The implementation of this technique follows the main steps of anagram technique there were (1) Finding the spesific material (2) Getting a words that can be formed to produce new word (3) Using the new words for learning vocabulary. Based on the observation and the questionnaire, the researcher found a positive effect in learning vocabulary using the anagram technique. The students became more enthusiastic and enjoyable in learning vocabulary and increase of students’ participation in the class. Additionally, the anagram technique can help to motivate the students to enrich vobabulary. Keywords: Anagram, Vocabulary